2012
DOI: 10.1387/ijdb.120146sc
|View full text |Cite
|
Sign up to set email alerts
|

The role of Akt signalling in the mammalian ovary

Abstract: The serine/threonine protein kinase Akt is involved in many cellular processes including cell growth, survival, proliferation and metabolism. Akt activity is modulated downstream of phosphatidylinositol-3-kinase (PI3K) in response to different extracellular stimuli. In the mammalian ovary, Akt collaborates with other kinases in the regulation of coordinate follicle and oocyte development. Akt determines the pool of primordial follicles and the transition from quiescent to growing phase. In addition, the kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 49 publications
3
55
0
1
Order By: Relevance
“…In C. gigas females at stage 3, compared with males and other stages, a significant increase of AKT mRNA levels was demonstrated. This observation supports the hypothesis that glucose metabolism is involved in vitellogenesis and/or in the late maturation stage in oyster, as demonstrated in vertebrates and fishes [114,115].…”
Section: Suggested Roles Of Creb Pi3k and Akt In Oyster Reproductionsupporting
confidence: 90%
“…In C. gigas females at stage 3, compared with males and other stages, a significant increase of AKT mRNA levels was demonstrated. This observation supports the hypothesis that glucose metabolism is involved in vitellogenesis and/or in the late maturation stage in oyster, as demonstrated in vertebrates and fishes [114,115].…”
Section: Suggested Roles Of Creb Pi3k and Akt In Oyster Reproductionsupporting
confidence: 90%
“…3). These results are in consonance with the deregulation of the PI3K/AKT pathway found in FXPOI females, as it is well known that this pathway can regulate many aspects of cell function (Cecconi et al, 2012). In this scenario, Lu et al (2012) found an increased apoptosis of follicle cells and an alteration of the AKT signaling cascade in ovaries of the FMR1 knock-in model.…”
Section: Discussionsupporting
confidence: 83%
“…1). Several lines of evidence have indicated that the PI3K/AKT gene family is critical regulator of follicle growth, differentiation and survival (Cecconi et al, 2012). In fact, lack of basal level of PI3K activation leads to the premature depletion of the pool of primordial follicles and to the development of POI (Reddy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion has been further confirmed by the similar levels of β-catenin and by the absence of pAKT and p53 in FT of control and hyperstimulated groups. In humans, the abnormal activation of the PI3K/AKT pathway [34] and increased nuclear β-catenin levels have been described to occur in OC [35]. Also in mice, high-grade serous OC can arise from the FT following deletion of PTEN, a negative regulator of PI3K pathway [36].…”
Section: Discussionmentioning
confidence: 99%